Socioeconomic disparities in children's posture defects: a comparison between private and public educational institutions - Lukasz Kolodziej; Sebastian Kwiatkowski; Magda Gebska; Ireneusz Walaszek; Karolina Skonieczna-Żydecka (PAGEPress Publications, 2024)
The topic of risk factors for posture pathology in Polish children is relevant at present, as it is insufficiently studied and reflects the need to investigate the relationship between family socioeconomic status and the occurrence of posture defects, to develop relevant prevention and treatment strategies in the context of current socioeconomic conditions in Poland. The research aims to study posture defects in children depending on their socioeconomic status in the example of private and public schools. A comparison of the prevalence of deformities and posture disorders of participants in private and public educational institutions from 2017 to 2020 is presented. Theoretical research methods (literature analysis, generalisation); empirical methods (study of other researchers' experience), statistical analysis, and graphical presentation of data were used. More than 1300 Polish schoolchildren from private and public schools took part in this cross-sectional study. The most common problems were flat feet (54.73%), calf muscle contracture (44.30%), and valgus deformity (21.22%). The least common problems were funnel chest (0.37%), cavus foot (0.10%), and hammer toe deformity (0.04%). The general trend shows that problems with flat feet and calf muscle contracture were more common among participants in both types of educational institutions. There was a general trend of increasing the number of nosological forms per patient in both private and public institutions over a period of three years. Private institutions had significantly fewer cases of one patient having more than one nosological form as compared to public institutions.